PENGARUH MODAL INTELEKTUAL DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA EFEK SYARIAH - ISLAMIYAH, SYUWAIBATUL (Jurnal Akuntansi AKUNESA, 2015)
The study aims to analyze the influence of intellectual capital and corporate governance to financial performance. The model that used to measure intellectual capital was using Modified Value Added Intellectual Coefficient (M-VAIC). M-VAIC component consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), andCapital Employed Efficiency (CEE). Corporate governance was measured by using three proxies proportion of independent board, audit commite, institusional ownership. Financial performance was measured by using ROA and ROE.This research is quantitative research and uses linear regression for data analysis. The data that was used in this research is secondary data and selected by using purposive sampling. The sample consists of 33 manufacturing companies which in list of Indonesia Sharia Stock during four years (2010-2013).The results showed that SCE, CEE, Audit Committe have significant effect on ROA and ROE. RCE negatively effect on ROA and ROE. Meanwhile, HCE, proportion of independent board doesn’t effect on financial performance (ROA and ROE). Institusional ownership effect on ROE. Keywords: Intellectual Capital, Modified Value Added Intellectual Coefficient (M-VAIC), corporate governance, financial performance.